Optimal shapes in multi-stages hot forging processes - Catarina F. Castro (2009)
The main purpose of this work is to control uncertainties during the forming process. Initialtemperature of the billet, friction between dies and billet and variations in the forging set uptogether with cooling rate are the main factors affecting the final part dimensions.Considering friction and die stroke length to be random variables, an attempt is made toanalyze the output data based on a large number of sets acquired with a finite element analysiscomputer model. The analysis of uncertainties associated to optimal multi-stage hot forgingwill drive to the robust design of forging process parameters.